2020
DOI: 10.1016/j.energy.2020.117227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon-based nanoparticles on the ignition, combustion and flame characteristics of crude oil droplets

Abstract: The use of in-situ burning (ISB) as a clean-up response in the event of an oil spill has generated controversy because of unburned hydrocarbons and products of incomplete combustion left behind on an ISB site. These substances threaten marine life, both in the ocean and on the ocean floor. Treating crude oil as a multicomponent liquid fuel, this manuscript investigates the effect of carbon-based nanomaterials, acetylene black (AB) and multi-walled carbon nanotube (MWNT), on the combustion and flame characteris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 40 publications
(61 reference statements)
3
4
0
Order By: Relevance
“…As can be seen, the effects of these two competing mechanisms droplet equivalent diameter cancel out, leading to a nearly constant of the droplet equivalent during 0. This observation is expected and is consistent with the results in literature for pure ethanol [57], α-methylnaphthalene [102], and Bakken crude oil [10].…”
Section: Contribution Of Atomization To Doped Ethanol Burning Ratesupporting
confidence: 94%
See 3 more Smart Citations
“…As can be seen, the effects of these two competing mechanisms droplet equivalent diameter cancel out, leading to a nearly constant of the droplet equivalent during 0. This observation is expected and is consistent with the results in literature for pure ethanol [57], α-methylnaphthalene [102], and Bakken crude oil [10].…”
Section: Contribution Of Atomization To Doped Ethanol Burning Ratesupporting
confidence: 94%
“…The maximum increase of the ignition delay for the loading concentration of 0.1% are 20.9, 16.8, and 16.6% pertaining to ethanol droplets doped with pGO, rGO, and hGO, respectively. The increase in the ignition delay of liquid fuels doped with carbonaceous nanomaterials is consistent with the observations reported in [9,10,13]. It is speculated that, generally, the presence of the carbonaceous nanomaterials increases the absorption of the heat generated by the flame without an immediate increase in the droplet temperature.…”
Section: Ignition Delaysupporting
confidence: 88%
See 2 more Smart Citations
“…Hao et al [53] found that aluminium (Al) nano-additives had a strong oxygen extraction ability and could significantly reduce the induction time and energy required for catalytic exothermic reactions. Singh et al [54] found that carbon-based single-walled nanotubes and multi-walled nanotubes could dramatically increase the ignition rate, ignition delay period, and extend the total combustion time. Therefore, it can be concluded that nano additives are very promising in fuels.…”
Section: Nano-additives: a Very Promising Fuel Additivementioning
confidence: 99%